Prajuritan Dance as a Medium for Anti-Corruption Character Education: A Phenomenological Study in Banyubiru Village - Emmanuel Satyo Yuwono; Sunardi Sunardi; Winston Lovevinzy Kakampu (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study examines the Prajuritan dance as an educational tool for fostering an anti-corruption character within the community of Banyubiru Village in Semarang Regency. Using a qualitative, phenomenological approach, the research explores the subjective experiences of artists, including dancers, trainers, and local cultural figures. Data were collected through in-depth interviews, participatory observation, and documentary studies, and were analysed using thematic analysis. The findings suggest that the Prajuritan dance embodies strong anti-corruption values, such as integrity, responsibility, self-discipline, and honesty. These values are not explicitly taught, but rather internalised through repeated cultural practices, the narrative structure of the dance, and collective community engagement. The study highlights the potential of traditional arts to serve as an effective ethical space for character education, particularly in community-based efforts to prevent corruption. Incorporating local arts into anti-corruption education strategies can reinforce a value ecosystem that is contextualised and grounded in the community's social experiences.